Bakhtin e o Círculo: línguas, discursos, gêneros e produção de sentido - Brait, Beth; Pistori, Maria Helena Cruz; Lopes-Dugnani, Bruna; Melo Júnior, Orison Marden Bandeira de (Bakhtiniana. Revista de Estudos do Discurso, 2020)
Editorial